Analysis of the performance of adaptive arrays with autual coupling compensation - LI Rong-feng 1; WANG Yong-liang 1; DAI Ling-yan 1; DING Qian-jun 1 (Tongxin xuebao)
The performance of adaptive arrays with mutual coupling compensation was analyzed in detail.It was indicated that the adaptive array was able to suppress interference thoroughly.The output power of noise,however,was influenced by the direction of beam scanning,which caused the degradation of the output signal-to-interference-plus-noise ratio（SINR） of the adaptive array.Therefore,the thermal noise is responsible for degrading the output SINR of adaptive arrays after mutual coupling compensation.The conclusions were further demonstrated by the simulation results.